International Quit and Win: successful global action for smoking cessation - Korhonen, T; Puska, P (Central European journal of public health, 2000)
Quit and Win has rapidly grown in popularity as a practical international smoking cessation activity. This is likely to be due to Quit and Win's unique, positive approach to a problem that is receiving increasing attention worldwide as a major health threat. The campaign is also a concrete channel for large international health collaboration, which is necessary considering the global nature of marketing efforts of the tobacco industry. Based on encouraging experiences of three previous international campaigns in 1994, 1996 and 1998, the next International Quit and Win will be organized in 2000. It will be larger than ever and support the new WHO Tobacco-Free Initiative.
Keywords: Program Evaluation; Smoking Cessation; hodnocení programu; retrospektivní studie; Global Health; Humans; celosvětové zdraví; lidé; Retrospective Studies; odvykání kouření